2015
DOI: 10.3727/096368915x687534
|View full text |Cite
|
Sign up to set email alerts
|

Bone Marrow-Derived Mesenchymal Stem Cells and Their Conditioned Medium Attenuate Fibrosis in an Irreversible Model of Unilateral Ureteral Obstruction

Abstract: The therapeutic potential of mesenchymal stem cells (MSCs) and their conditioned medium (MSC-CM) has been extensively studied. MSCs can repair tissue, reduce local inflammation, and modulate the immune response. Persistent renal tubular interstitial inflammation results in fibrosis and leads to chronic kidney disease (CKD). Unilateral ureteral obstruction (UUO) is a very well-accepted renal fibrosis model. In this study, we evaluated factors influenced by the administration of MSCs or MSC-CM in the UUO model. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
34
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 32 publications
(38 reference statements)
2
34
0
Order By: Relevance
“…Although MSC therapy is becoming an attractive strategy for renal repair, most clinical trials involve only early phases of kidney disease (28), and the potential of MSC-based therapy to prevent or ameliorate CKD is only beginning to be elucidated. Several recent animal studies show the capacity of exogenously administered MSCs to dramatically reduce tubulointerstitial fibrosis, preserve peritubular capillary density, and prevent epithelial mesenchymal transition in multiple different models of chronic renal injury (2,3,5,22,26,31,38). Our results support these observations and demonstrate a significant reduction in obstruction-induced collagen I and III mRNA expression, collagen deposition, fibronectin and α-SMA expression, and fibronectin and α-SMA deposition in the kidney in the presence of MSCs.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Although MSC therapy is becoming an attractive strategy for renal repair, most clinical trials involve only early phases of kidney disease (28), and the potential of MSC-based therapy to prevent or ameliorate CKD is only beginning to be elucidated. Several recent animal studies show the capacity of exogenously administered MSCs to dramatically reduce tubulointerstitial fibrosis, preserve peritubular capillary density, and prevent epithelial mesenchymal transition in multiple different models of chronic renal injury (2,3,5,22,26,31,38). Our results support these observations and demonstrate a significant reduction in obstruction-induced collagen I and III mRNA expression, collagen deposition, fibronectin and α-SMA expression, and fibronectin and α-SMA deposition in the kidney in the presence of MSCs.…”
Section: Discussionsupporting
confidence: 87%
“…Several studies have demonstrated that MSCs can protect against acute and chronic renal injury (1,8,28), and, while the mechanism of MSC-induced renal protection remains unknown, recent studies suggest that a significant component of MSC's protective and reparative function resides in their paracrine activity. MSCs can secrete a number of growth factors and cytokines that are important for angiogenesis and cytoprotection and have been demonstrated to prevent tubulointerstitial fibrosis during chronic unilateral ureteral obstruction (UUO) (2,5,9).…”
mentioning
confidence: 99%
“…More importantly, if the factors secreted by the MSC can slow the progression of CKD, this can overcome the drawbacks of allogeneic MSC transplantation, such as inconvenience, immunological rejection, and MSC tumorigenesis. 9 Previous studies have shown that MSC-CM promotes proliferation and migration of alveolar epithelial cells under septic conditions. 10 However, few studies have been specially designed to study the effects of MSC secretion factors in kidney diseases.…”
Section: Introductionmentioning
confidence: 99%
“…This paracrine function laid the foundation for the use of MSC‐secreted factors in cell‐free treatment strategies. More importantly, if the factors secreted by the MSC can slow the progression of CKD, this can overcome the drawbacks of allogeneic MSC transplantation, such as inconvenience, immunological rejection, and MSC tumorigenesis . Previous studies have shown that MSC‐CM promotes proliferation and migration of alveolar epithelial cells under septic conditions .…”
mentioning
confidence: 99%
“…Growing evidence supports its feasibility and potential application for cardiovascular and renal therapy since these pluripotent cells are rich sources of cytokines and growth factors that can promote tissue healing and slow or halt the progression of tissue damage. Administration of exogenous stem cells could prevent and promote renal recovery via modulation of the immune system, release of paracrine factors, and production of microvesicles with powerful anti-inflammatory and anti-fibrotic effects 127, 128 .…”
Section: Therapeutic Strategies: Is Protection Of Renal Microvessels mentioning
confidence: 99%